Consumption oxygen by sStrains of espundia and uta (Leishmania) with monosaccharides - Aurazo R., Margarita (1974)
This is a comparative study of respiration and mO:1osaccarid action (Glucose, Fructuose, Galactase ond Mannose) about oxygen consumption between two strains of Leishmania isolated from patients with cutaneous (uta) and muco-cutaneous leishmaniasis (espundia) from Peru.